DEPRESSION LEVELS AND IT’S RELATION WITH CLINICAL SYMPTOMS IN YOUNG WOMEN WITH CHRONIC FATIGUE SYNDROME - Remzi Çevik; Suat Acar; Ali Gür; Kemal Nas; A. Jale Saraç (Archives of Rheumatology, 2004)
Chronic Fatigue Sydrome (CFS) is a chronic, disabling, musculoskeletal system illness which lasts more than six months with fatigue and musculoskeletal pain, psychiatric symptoms and mostly occured in women. Depression is a psychiatric disorder which is often seen with CFS. The objective of this study was to investigate depression levels in premenapousal female patients with CFS; and to define its’ relation with symptomatic features and number of tender points acount. Sixty one (61) premenapousal female patients identified with CFS and thirty five (35) healthy women were taken in this study according to Atlanta CDC (Center for Disease and Control) criteria in 1994. Beck depression scales of these two groups were measured and patients were examined according to their symptomatic features, tender points and widespread musculoskeletal aching. In our study, symptomatic features, Beck scores and number of tender points were higher in the patient group comparing with control group (p<0.001). There were significant differences between patients who had Beck scores ≥17 and <17 in number of tender points, arthralgia and sleep disturbences(p<0.05 and p<0.01). There were significant correlation between Beck scores and tender point account, sleep disturbences, sore throat, arthralgia and muscle weakness (p<0.001 ve p<0.05 ). Our study indicates that patients with CFS have high depression level and tender point count. Patients with high depression level have higher tender point count, sleep disturbences and arthralgia rates compared patients with low depression level. Depression and fibromyalgia should be taken into consideration in diagnosis and managing of CFS.